2010
DOI: 10.18553/jmcp.2010.16.8.578
|View full text |Cite
|
Sign up to set email alerts
|

Results from a Mailed Promotion of Medication Reviews Among Department of Defense Beneficiaries Receiving 10 or More Chronic Medications

Abstract: • Interventions that involve collaboration among patients, physicians, and/or pharmacists have been significantly associated with improvements in medication adherence, persistence, and attainment of clinical goals for specific disease states, as well as reductions in the number of medications or the number of highrisk drugs or drug combinations in a patient's regimen. • The 2009 National Committee for Quality Assurance physician metric for medication review among older adults specifies that "counseling about m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…15.7% of their sample consented to participate in a medication review, and of these, only 9.7% returned a completed survey following the review. 21 This strengthens the conclusion that using informational mailings as a means to garner MTM participation is not an effective use of resources.…”
Section: Discussionsupporting
confidence: 58%
“…15.7% of their sample consented to participate in a medication review, and of these, only 9.7% returned a completed survey following the review. 21 This strengthens the conclusion that using informational mailings as a means to garner MTM participation is not an effective use of resources.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, prior research has described limited success with passive approaches. 8 Interestingly, telephone calls resulted in more MTM appointments than the other "active" approach (i.e., face-to-face). While not significantly significant, this may have contributed to the nonsignificant difference between the dichotomized active and passive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…36,38,39,42 However, surveys conducted on patients who received pharmacist-provided MTM services revealed that the majority of these patients felt more knowledgeable about their medications and were satisfied with the program. 37,41,43 Furthermore, patients who recently visited a physician concerning a drug-related problem or regularly visit clinic pharmacies have been reported to be more favorable toward pharmacists’ provision of MTM services. 36 Patients’ willingness to pay for MTM services have also been shown to be low, with no significant relationship between patient’s willingness to pay for MTM services and complexity of the medication regimen.…”
Section: Summary Of Surveysmentioning
confidence: 99%
“…Pharmacists, 12 28 pharmacy students, 29 31 physicians, 32 35 and patients 36 43 have been surveyed on issues centered around implementation, enrollment, delivery, compensation, attitudes, perception, satisfaction, willingness to pay, training needs, skills, and knowledge as these relate to the provision of MTM services. While each study reveals findings that may have the potential to provide insight on how to restructure the design and delivery of MTM services, there is not one document that summarizes these findings into a single report in order to provide comprehensive information for future research purposes.…”
Section: Introductionmentioning
confidence: 99%